STEM-ESD Integration in E-Module to Improve Critical Thinking Skills - Rika Marlina; Irvan Permana; Dadang Jaenudin; Indriyani Rachman; Toru Matsumoto (Yayasan Keluarga Guru Mandiri, 2026)
Observations and literature reviews indicate that vocational school students' critical thinking skills remain low, even though these skills are important for vocational graduates. One reason is the limited availability of interactive teaching materials for the IPAS Project subject. This study aims to develop a STEM-ESD-based e-module for the IPAS Project on Soil Pollution to improve the critical thinking skills of Year 10 vocational school students. The study uses the Research and Development (RD) method with the ADDIE model. The e-module was developed using Heyzine Flipbook. The validation results showed that the e-module was highly valid, with a score of 90% from subject matter experts, 92% from media experts, and 93% from language experts, as well as a very practical response from teachers (93%). The implementation of the e-module resulted in increased critical thinking skills, with an N-Gain score of 0.67 and very positive student responses. This e-module is suitable for use as an innovative teaching material that supports student-centred learning and sustainable education.